PREVALENCE OF POTENTIAL DRUG-DRUG INTERACTIONS AMONG PROLANIS TYPE 2 DIABETES PATIENT WITH HYPERTENTION IN PRIMARY HEALTH CARE: CROSS SECTIONAL STUDY - Primayanti Nurul Ilmi; Hilda Fauziah; Annisa Farida Muti (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2022)
Potential drug–drug interactions (pDDIs) are important factors resulting in adverse drug reactions or therapeutic failure. Therefore, pDDIs need to be identified to prevent the related risk and improve drug safety. The objective of this study was to assess the prevalence of pDDIs among Prolanis type 2 diabetes patients with hypertension. Additionally, this study aims to categorize and rate the identified pDDIs according to mechanism, severity and level of significance. This cross-sectional study was conducted at Kramat Jati District primary health care. Patient medical records from January to June 2018, were analysed using Drug Interaction Facts and Stockley’s Drug Interaction for pDDIs with a total 138 patients identified. pDDIs were detected in 35 patients (25.4%), with a total 57 interactions. They were clinically relevant with major (42.1%) in severity and refer to level one of significance (42.1%). The interaction type was unknown (64.9%), pharmacodynamic (64.9%) and pharmacokinetic (12.2%) respectively. The most common interaction was amlodipine-simvastatin in 19 cases (33.3%). Prolanis type 2 diabetes patients with hypertension were at risk to pDDIs, particularly to major pDDIs. Screening of prescriptions and medical records for pDDIs also monitoring of pharmacotherapy in terms of response and associated adverse drug events will contribute to patient safety.